2012
DOI: 10.1007/s10059-012-2246-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional HSF1 Requires Aromatic-Participant Interactions in Protecting Mouse Embryonic Fibroblasts against Apoptosis Via G2 Cell Cycle Arrest

Abstract: The present study highlighted the aromatic-participant interactions in in vivo trimerization of HSF1 and got an insight into the process of HSF1 protecting against apoptosis. In mouse embryonic fibroblasts (MEFs), mutations of mouse HSF1 (W37A, Y60A and F104A) resulted in a loss of trimerization activity, impaired binding of the heat shock element (HSE) and lack of heat shock protein 70 (HSP70) expression after a heat shock. Under UV irradiation, wildtype mouse HSF1 protected the MEFs from UV-induced apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Our results showed that HSF1 also reversed the expression of HSPs, while it relieved apoptosis and ER stress induced by amyloid-b. HSPs are needed by HSF1 in protecting against apoptosis [31]. Overexpressing of HSP27 reduces amyloid-b-mediated cell death and protects against amyloid-b-induced damage [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that HSF1 also reversed the expression of HSPs, while it relieved apoptosis and ER stress induced by amyloid-b. HSPs are needed by HSF1 in protecting against apoptosis [31]. Overexpressing of HSP27 reduces amyloid-b-mediated cell death and protects against amyloid-b-induced damage [32].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid-b (Ab [25][26][27][28][29][30][31][32][33][34][35] ) was purchased from Bioss (Beijing, China) and dissolved in sterile water at the concentration of 0.94 mM. This stock solution was stored at -20°C but was kept at 37°C for 72 h before use.…”
Section: Methodsmentioning
confidence: 99%
“…Since HSPA7 and A13 are also known as inducible members of HSPs (Leung et al, 1992;Otterson et al, 1994), it can be postulated that these HSPs are not induced in subjects with ASP or acute heart failure as robustly as in those with TI. Rapid gene tran-A B scription of inducible HSP mRNAs primarily lies under the control of HSF1, acting on downstream target genes bearing heat shock elements in their promoter region (Chang et al, 2012;Fujimoto and Nakai, 2010), other cis-elements in the promoters often contribute to differential modes of transcriptional induction in different cellular contexts as well as by exposure to different types and severities of stressful stimuli (Diller, 2006;Stetler et al, 2010). Therefore, it is reasonable that circumstances of death can differentially influence transcriptional induction of each member of the inducible HSPs, leading to alterations in postmortem mRNA profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, elevated HSP expression has been identified in upper epidermal cells and HSP70 was shown to protect against ROS- or UVB-induced cell death in keratinocytes [131,132]. Following this line, mutated heat shock factor (HSF1) incapable of conveying HSP70 transactivation failed to prevent UV-induced apoptosis in mouse embryonic fibroblasts [133]. Thus, HSP70 seems to represent another pro-survival factor in irradiated potentially cancerous skin cells.…”
Section: Uv Does Not Act Alone: Impact Of Heat Shock and Infrared mentioning
confidence: 99%